KAJIAN PENGENDALIAN EROSI PADA SUNGAI PEDES KABUPATEN BREBES - Wirawan, Andreas Raditya; Utama, Putra; Suharyanto, Suharyanto; Edisono, Sutarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Pedes River is one of a branch of Glagah River at Brebes Regency. The length of Pedes River is ±29.175 km and the catchment area is 46.565 km2. Most of resident at Pedes River work as miner of the C excavation material. Mining activity that continuously occure cause the slope of the river is quite big so the velocity of the water is raising. The velocity of the water at Pedes River cause erosion that occure along the river. This condition is compounded by meandered shape of the river and the riverbank is steep. Erosion that occure eroded riverbank and riverbed. The effect of erosion are the slope of the river grows bigger, and landslide at some place in the river. Check dam is one of the solution to minimize the slope of the riverbed. But for the comprehensive solution along the river, study about erosion control is needed to determine solution along the Pedes River.